Dictionary of cognitive science : neuroscience, psychology, artificial intelligence, linguistics, and philosophy - Houdé, Olivier (Psychology Press, 2004)
A translation of the renowned French reference book, Vocabulaire de sciences cognitives , the Dictionary of Cognitive Science presents comprehensive definitions in more than 120 subjects. Topics range from 'Abduction' to 'Writing', and each entry is covered from as many perspectives as possible within the domains of psychology, artificial intelligence, neuroscience, philosophy, and linguistics. The editor and his advisory board, each a specialist in one of these areas, have brought together 60 internationally recognized scholars to give the reader a comprehensive understanding of the most current and dynamic thinking in the cognitive sciences.